Liberalism and its values - Paxton, Marie (2012)
This dissertation seeks firstly to expose the fundamental difficulties associated with liberal attempts at conflict mediation, and subsequently to consider how these can be overcome through the development of post-liberalism and agonism. As highlighted by events such as the July 7th London bombings and the 2011 UK riots, values in pluralist society – such as those held by Marxist; feminist; religious; and ethnic groups - are often incompatible and incommensurable with one another. The dissertation aims to unearth liberal universalism as an aggravator of these pluralist tensions, increasing the potential for fundamentalism and the outbreak of conflict. It will argue that claims about the neutrality and universality of its principles, alongside its employment of a fixed public-private distinction, renders liberal universalism an oppressive theory that suppresses politics. Subsequent to forming this normative critique of liberal universalism, the dissertation will then examine post-liberal attempts to abandon neutrality and universality in favour of radical choice and contingency. Post-liberalism aims to provide a less oppressive alternative and to revive politics. However, I will suggest that post-liberal aspirations toward radical choice and contingency can neither overcome oppression, nor revive politics, unless it renegotiates the fixed public-private divide. The dissertation argues that agonism fills this gap by reworking the public-private distinction. It illustrates how agonism employs a similar rejection of liberal neutrality and universality, endorsing the same radical choice and contingency advocated by post-liberalism. The dissertation then considers how agonism builds on this through notions of agonistic respect and critical responsiveness, both of which allow it to renegotiate the public-private distinction. I will then discuss how renegotiation surmounts both the oppression of pluralist groups and the suppression of politics, encouraging citizens to engage publicly in the continual contestation of existing values. In so doing, the paper aspires to demonstrate how agonism builds on post-liberal advancements to offer us a less oppressive, more diverse alternative, rendering it a favourable conflict mediator to liberal universalism.